WS-TDD: uma abordagem ágil para o desenvolvimento de serviços WEB - Bissi, Wilson (2016)
Test Driven Development (TDD) is an agile practice that gained popularity when defined as a fundamental part in eXtreme Programming (XP). This practice determines that the tests should be written before implementing the code. TDD and its effects have been widely studied and compared with the Test Last Development (TLD) in several studies. However, few studies address TDD practice in the development of Web Services (WS), due to the complexity of testing the dependencies among distributed components and the specific characteristics of Service Oriented Architecture (SOA). This study aims to define and validate an approach to develop WS based on the practice of TDD, called WS-TDD. This approach guides developers to use TDD to develop WS, suggesting tools and techniques to deal with SOA particularities and dependencies, focusing on the creation of the unitary and integrated automated tests in Java. In order to define and validate the proposed approach, four research methods have been carried out: (i) questionnaire; (ii) practical experiment; (iii) personal interview with each participant in the experiment and (iv) triangulation of the results with the people who participated in the three previous methods. According to the obtained results, WS-TDD was more efficient compared to TLD, increasing internal software quality and developer productivity. However, the external software quality has decreased due to a greater number of defects compared to the TLD approach. Finally, it is important to highlight that the proposed approach is a simple and practical alternative for the adoption of TDD in the development of WS, bringing benefits to internal quality and contributing to increase the developers’ productivity. However, the external software quality has decreased when using WS-TDD.